Ruptured Left Gastric Artery Aneurysm Successfully Treated by Thrombin Injection: Case Report and Literature Review - S. Chandran; A. Parvaiz; A. Karim; I. Ghafoor; B. Steadman; N. W. Pearce; J.N. Primrose (The Scientific World Journal)
This short report describes the successful use of a new minimally invasive technique for the treatment of acute gastric artery aneurysm rupture. It emphasises the importance of persistence and multiple imaging modalities in the presence of gastrointestinal bleeding. The photographs and case history clearly illustrate the nonoperative management and highlight learning points for experienced surgeons and trainees alike in the management of this potentially fatal condition.